Gender political inclusion and democracy in Africa: Some empirical evidence - Tii Njivukuh Nchofoung; Simplice Asongu; Vanessa Tchamyou; Ofeh M. Edoh (African Governance and Development Institute (AGDI), 2022)
The objective of this study is to examine the effect of political inclusion on democracy in Africa. The results of the analyses through the OLS, system GMM, IV-Tobit and IV-2SLS show that gender political inclusion enhances democracy in Africa. This result is robust across alternative specifications of political inclusion and democracy. Besides, the results equally stood when controlled for colonisation and internal conflicts. In terms of policy implications, policymakers in Africa should enhance their fight for political inclusion as one of the gateways to promoting democracy. In this respect, national laws could be put in place, which impose gender quotas in political positions in every country. Equally, the African Union could sign a convention on these quotas for respective countries to ratify.
Keywords: I32; O55; P16; P43; P50; 330; Political inclusion; democracy; Africa